Atmospheric Sound Design in Games: Pacing Engagement and Environmental Storytelling - Collins, Callum Barnett (Auckland University of Technology, 2022)
Atmospheric Sound Design in Games: Pacing, Engagement, and Environmental Storytelling seeks to demonstrate that game pacing is a key factor in determining player investment in high-agency narrative elements, such as environmental storytelling, and that pacing can be manipulated through both level design and atmospheric sound design. This research seeks to further game sound research by producing artefacts that will serve as case studies for other designers and researchers. These artefacts will take the form of game prototypes which will explore game sound design and discover what techniques and tools effectively realise the potential of sound as a narrative device and engage the player in the narrative of a game world. The making processes of this research will follow an iterative design methodology, using the methods of conceptualisation, prototyping and evaluation. The case studies Flower, Darkwood and Limbo will form the basis of ideation for the prototypes and serve as a reference during iteration and development. These case studies will be used to analyse how sound can be incorporated into a game design process, to further understand its connection to level design and pacing.